Fractionation-Guided Antibacterial Screening of Selected Medicinal Plant Extracts Against Pathogenic Bacteria (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Fractionation and standardised antibacterial screening are viable concepts employed in separating active compounds in plant extracts that can hinder the growth of tested bacteria. Five plant samples were selected for fractionation, these includes rhizome extract of Curcuma longa, seed extract of Quercus infectoria, leaf extracts of Punica granatum, Terminalia catappa and Murraya koenigii. Nine strains of pathogenic bacteria were employed in this research: Listeria monocytogenes ATCC 19115, Staphylococcus aureus ATCC 700699, Escherichia coli O157:H7, Escherichia coli ATCC 25922, Salmonella Paratyphi ATCC 9150, Salmonella Typhi ATCC 14028, Vibrio alginolyticus ATCC 17749, Vibrio paraheamolyticus ATCC 17802 and Yersinia enterocolitica ATCC 23715. The MIC of the extracts was determined using microdilution broth method. The plant extracts were fractionated using paper chromatography. Mixture of butanol, acetic acid and distilled water was prepared in the ratio of 4:1:5. The mixture was used as the mobile phase. Only Fraction 6 of M. koenigii exhibited good MIC value of 62.5 µg/mL against L. monocytogenes and 31.25 µg/mL against S. aureus and E. coli O157:H7, but the rest of the fractions showed MIC value ranging from 125-1000 µg/mL. The findings of this study may be useful for developing new natural product-based therapy for pathogenic bacteria.
Keywords: Plant extracts; Antibacterial activity; Fractionation; Minimum inhibitory concentration (MIC); Pathogenic bacteria